The Inhibition Mechanism of Surfactant Composite for Mild Steel Corrosion in NaCl Solution - MK Harun; I Ismail; MZA Yahya (ASM Science Journal, 2021)
The corrosion inhibition of sodium deodecylbenzenesulfonate (SDBS) surfactant and ZnSO4 on mild steel in 0.05 M NaCl solution was conducted through the impedance spectroscopy and linear polarisation measurement. The inhibitors performance was measured separately and as a mixed composite of both at a ratio of 200:200 ppm. Results obtained from both these measurements indicate high corrosion inhibition of the mild steel substrates was achieved. Porosity calculation of the formed inhibition layer was done through the obtained linear polarisation data, and its dielectric properties were deduced from the impedance measurements. Two possible structures of the formed inhibitive layers are proposed. The first structure involved the formation of a stable but porous zinc oxide/hydroxide layer with the surfactant filling up the pores, thus forming a continuous inhibitive barrier film layer while the second, involved a formation of a continuous inhibitive barrier layer due to the chelation of the surfactant and ZnSO4 compounds. The results obtained also indicated that corrosion resistance induced by the inhibitive barrier layers is much more dependent on its charge transfer resistance properties rather than its dielectric properties and that the corrosion inhibition provided is not directly related to the double-layer capacitance values of the barrier layer.